2006
DOI: 10.1128/mcb.00556-06
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 Requires Tyrosine Sulfation for Ligand Binding and a Second Extracellular Loop Arginine Residue for Ligand-Induced Chemotaxis

Abstract: CXCR3 is a G-protein-coupled seven-transmembrane domain chemokine receptor that plays an important role in effector T-cell and NK cell trafficking. Three gamma interferon-inducible chemokines activate CXCR3: CXCL9 (Mig), CXCL10 (IP-10), and CXCL11 (I-TAC). Here, we identify extracellular domains of CXCR3 that are required for ligand binding and activation. We found that CXCR3 is sulfated on its N terminus and that sulfation is required for binding and activation by all three ligands. We also found that the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 52 publications
10
127
1
Order By: Relevance
“…Here we have shown not only that tyrosines 27 and 29 are sulfated but also that these sulfated moieties are critically important for binding native IP-10. Our data that double sulfated tyrosines contribute to ligand binding are inconsistent with the previous report showing that single mutation of tyrosine 27 or 29 of CXCR3 decreases its ability to bind its ligands, including IP-10 [36] . There are several possible explanations for these inconsistencies.…”
Section: Discussioncontrasting
confidence: 57%
“…Here we have shown not only that tyrosines 27 and 29 are sulfated but also that these sulfated moieties are critically important for binding native IP-10. Our data that double sulfated tyrosines contribute to ligand binding are inconsistent with the previous report showing that single mutation of tyrosine 27 or 29 of CXCR3 decreases its ability to bind its ligands, including IP-10 [36] . There are several possible explanations for these inconsistencies.…”
Section: Discussioncontrasting
confidence: 57%
“…The N terminus of the receptor is also a site for PTM providing additional negative charge such as sulfation and O-linked glycosylation, both of which have been reported to be crucial for ligand binding to the receptors CCR5, CX3CR1 and CXCR3 [16][17][18][19]. The activation event following ligand tethering is postulated to occur in close proximity to the cell membrane and involve the disruption of interactions between side chains of neighbouring TM helices by the chemokine N terminus [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…2). Coupled with this, we also explored the role of posttranslational modifications (PTM) of this receptor region, since studies of CCR5, CX3CR1 and CXCR3 have shown that O-linked oligosaccharides and sulfated tyrosine residues within the N terminus play an important role in chemokine binding [16][17][18][19]. The impact of PTM on CXCR6 function was probed using both site-directed mutagenesis and pharmacological inhibitors of glycosylation and sulfation.…”
Section: Probing the Cxcr6:cxcl16 Interaction By Mutagenesis Of The Cmentioning
confidence: 99%
“…13,20 In contrast, the glutamate receptor 21 and heat shock proteins 22 are involved in other cellular functions. Based on the observation that CXCR3 activities are potentially relevant to CD pathogenesis, we pursued the possible role of CXCR3 as a receptor for PT-gliadin.…”
Section: Identification Of Cxcr3 As the Pt-gliadin Intestinal Bindingmentioning
confidence: 99%